PENTINGNYA KOMPETENSI GURU GUNA MENGHADAPI SISTEM REKRUTMEN BARU “MARKETPLACE GURU” - Nadif Maialfatih (CV. ADIBA AISHA AMIRA, 2024)
The Ministry of Education, Culture, Research and Technology, Nadiem Anwar Makarim issued a new recruitment system, namely the